INCORPORATION OF COMPLEX MOLECULES AND SUPRAMOLECULAR STRUCTURES INTO METAL-ORGANIC FRAMEWORKS - Newman, M. R. (2023)
In this thesis, three different supramolecular frameworks will be described. The first is a novel naphthalene diimide (NDI) metal-organic framework-based, flexible, nanotube structure. The crystal structure is reported and described. The structure was spectroscopically probed to investigate the formation of an NDI radical upon exposure to UV/Visible radiation and investigated by Raman spectroscopy to measure chemical changes upon mechanical bending of the nanotubes. In the second section, two tetra-acid rotaxanes, TAR4 and TAR8 are synthesised and analysed by proton NMR and the single X-ray crystal of the former, is detailed. Once synthesised, attempts were made to incorporate these into metal-organic frameworks motifs through several methods. Two other diacid rotaxane syntheses were also started and the preliminary reactions to form them detailed. The final chapter details the synthesis of a naphthalene diimide/porphyrin [2]handcuff rotaxane; which was planned and started, with these discussed.